Effectiveness of a fluid chart in outpatient management of suspected dengue fever: A pilot study - Nasir, N.H.; Mohamad, M.; Lum, L.C.S.; Ng, C.J. (Public Library of Science, 2017)
Introduction: Dengue infection is the fastest spreading mosquito-borne viral disease in the world. One of the complications of dengue is dehydration which, if not carefully monitored and treated, may lead to shock, particularly in those with dengue haemorrhagic fever. WHO has recommended oral fluid intake of five glasses or more for adults who are suspected to have dengue fever. However, there have been no published studies looking at self-care intervention measures to improve oral fluid intake among patients suspected of dengue fever. Objective: To assess the feasibility and effectiveness of using a fluid chart to improve oral fluid intake in patients with suspected dengue fever in a primary care setting. Methods: This feasibility study used a randomized controlled study design. The data was collected over two months at a primary care clinic in a teaching hospital. The inclusion criteria were: age > 12 years, patients who were suspected to have dengue fever based on the assessment by the primary healthcare clinician, fever for > three days, and thrombocytopenia (platelets < 150 x 109/L). Both groups received a dengue home care card. The intervention group received the fluid chart and a cup (200ml). Baseline clinical and laboratory data, 24-hour fluid recall (control group), and fluid chart were collected. The main outcomes were: hospitalization rates, intravenous fluid requirement and total oral fluid intake. Findings: Among the 138 participants who were included in the final analysis, there were fewer hospital admissions in the intervention group (n = 7, 10.0%) than the control group (n = 12, 17.6%) (p = 0.192). Similarly, fewer patients (n = 9, 12.9%) in the intervention group required intravenous fluid compared to the control group (n = 15, 22.1%), (p = 0.154). There was an increase in the amount of daily oral fluid intake in the intervention group (about 3,000 ml) compared to the control group (about 2,500 ml, p = 0.521). However, these differences did not reach statistical significance. Conclusion: This is a feasible and acceptable study to perform in a primary care setting. The fluid chart is a simple, inexpensive tool that may reduce hospitalization and intravenous fluid requirement in suspected dengue patients. A randomized controlled trial with larger sample size is needed to determine this conclusively. Trial registration: International Standard Randomized Controlled Trial Number (ISRCTN) Registry ISRCTN25394628 http://www.isrctn.com/ISRCTN25394628.